Reconstructing Gender Justice in Hadith: A Theological Reading Through Nur Rofiah’s Women’s Hakiki Justice Approach - Hamidah, Najlah; Muhibbin (Journal of Ushuluddin and Islamic Thought, 2024)
This article explores the theological foundations for gender justice within Islamic tradition by reinterpreting a prophetic tradition through the lens of hakiki justice, a conceptual framework developed by Indonesian scholar Nur Rofiah. The study focuses on a hadith narrated by Imam al-Tirmidhī (No. 1162), which, while traditionally viewed as a normative ethical teaching on family relations, is examined here for its potential to support an emancipatory reading when contextualized within women’s lived experiences. Employing the maʿānī al-ḥadīth (semantic analysis) approach, this research argues that even non-explicitly transformative hadith can serve as a theological basis for advancing gender justice when interpreted through a critical, contextual, and gender-aware framework. The study responds to critiques of patriarchal bias in the commentary of hadith and contributes to the broader discourse on Islamic feminist hermeneutics by expanding the use of Nur Rofiah’s approach beyond Qur’anic texts. Ultimately, this paper demonstrates that re-reading hadith with attention to both context and justice principles can support more inclusive and equitable understandings of Islam.